Kant, Causal Judgment & Locating the Purloined Letter - R. Westphal, Kenneth (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Kant’s account of cognitive judgment is sophisticated, sound and philosophically far more illuminating than is often appreciated. Key features of Kant’s account of cognitive judgment are widely dispersed amongst various sections of the Critique of Pure Reason, whilst common philosophical proclivities have confounded these interpretive difficulties. This paper characterises Kant’s account of causal-perceptual judgment concisely to highlight one central philosophical achievement: Kant’s finding that, to understand and investigate empirical knowledge we must distinguish between predication as a grammatical form of sentences, statements or (candidate) judgments, and predication as a (proto-)cognitive act of ascribing some characteristic(s) to some localised particular(s). With Kant’s finding in view, I then elucidate how we have occluded his achievement. My results are not merely interpretive, but philosophical, because they show that Kant’s account of perceptual judgment accords with – and indeed justifies – a central and sound point regarding language, thought and reference advocated by apparently unlikely philosophical comrades. These finding highlight some methodological cautions which require re-emphasis today.